"Милая мама...": емпативна інтерпретація епістолярного образу Олени Пчілки - Кочерга, С.О. (Слово і Час, 2019)
Стаття присвячена з'ясуванню візії Олени Пчілки в епістолярному спадку молодшого
покоління Косачів, насамперед сина Михайла. Проаналізовано своєрідність комунікації матері
з дітьми, емпативні оцінки характеру письменниці, що багатогранно виявлявся в родинному
колі. Наголошено на концепті мовчання, який став важливим маркером внутрішніх конфліктів
у сім'ї та згодом, зокрема, сублімувався у творчості Лесі Українки як дискурс комунікативного
розриву. Доведено, що попри контроверсійність педагогічних засад Олени Пчілки діти виявляли
максимальну толерантність до її комплексів, усвідомлюючи виняткову роль матері в їхньому
особистісному становленні. The paper deals with empathetic characteristics of Olena Pchilka’s personality in the family letters.
The correspondence of the writer’s children, in particular Mychailo and Lesia, contains a number of
details for the psychological portrait of Olena Pchilka; it captures her various emotional states and
reactions, allows defining the communicative frames that dominated in the family.
The researcher traces the formation of a specific Olena Pchilka’s cult, which concerned her roles
of a writer, public person, and mother. It is confirmed by numerous enthusiastic and thankful words
in the letters of her children. However, the main attention is paid to the synthesis of self-sacrifice and
authoritarianism in Olena Pchilka’s family pedagogy.
Communication at distance between Lesia Ukraiinka and her mother turned into an experiment
of modeling the image of a national writer. At the same time, the letters testify to the fact that Olena
Pchilka recognised the unique gift and powerful intelligence of her daughter Lesia Ukraiinka. The
mother managed to establish quite friendly relations with her elder children, but Pchilka’s desire to
control the emotional world of young Kosaches, her insistent interpretation of it, and the fear of other
people’s excessive infiuence on her children caused long-lasting confiicts, accompanied by ‘tactics of
silence’. These destructive tactics resulted in emotional traumas, which, in particular, were sublimated
in the literary world of Lesia Ukraiinka as a discourse of communicative rupture (“Advocate Martian”,
“Johanna, Chusa’s Wife”, “Aisha and Mohammed”, “Babylonian Captivity”, etc.).
It should be noted that children tried to tolerate their mother’s dependence on her psychological
complexes and insistent self-isolation, understanding the unique role of Olena Pchilka in their personal
development.